Error Analysis of ESL Students’ Writing at Secondary Level in Government Girls High School, Kityari - Maryam Bibi; Sana Nazir; Mehak Asif; Haseeba Bibi (Policy Journal of Social Science Review, 2026)
This study investigates the common writing errors made by secondary-level students in Class 9 and Class 10, aiming to identify the types of mistakes and their underlying causes. Researchers analyzed writing samples from fifteen students, utilizing Pit Corder’s Model of Error Analysis to assess their performance. The analysis revealed six primary categories of errors: omission, addition, misordering, misinformation, overt errors, and covert errors. Notably, omission and misordering emerged as the most frequent mistakes, while addition was less common. The findings highlighted that overt errors were more prevalent than covert errors in the students' writing. The results indicated that many errors stem from students' limited understanding of English grammar, vocabulary, and sentence structure. Additionally, the influence of their native language often leads to direct translations that disrupt proper English sentence formation. These issues pose significant challenges for learners trying to produce grammatically correct and coherent sentences. The insights from this research can help English teachers recognize the specific writing difficulties faced by secondary-level students, enabling the development of more effective teaching strategies and activities to enhance grammar, sentence structure, and overall writing skills. Furthermore, the study serves as a resource for future researchers interested in English writing, error analysis, and second-language acquisition at the secondary school level. Keywords: Error Analysis, English Writing, Pit Corder’s Model, Secondary-level Students, Class 9, Class 10, GHHS Kityari. https://doi.org/10.5281/zenodo.21848671